DESAFIOS DAS FAMÍLIAS NO DECORRER DA PANDEMIA POR COVID-19: PERCEÇÕES DE ENFERMEIROS. - Silva, Margarida; Barros, Teresa; Loureiro, Helena; Ferreira, Manuela; Henriqueta Figueiredo, Maria (RIIS: Revista de Investigação & Inovação em Saúde, 2023)
Background: the COVID-19 Pandemic has been putting challenges to families, and may represent a threat to the functionality of the family system, implying changes in the family structure and functioning, namely in the routines and patterns of interaction. Objectives: to analyze the perception of primary health care nurses about the resources and weaknesses of the families' internal environment, relating to the effects of the Pandemic on family functioning. Methodology: cross sectional study based on a qualitative approach. An online questionnaire was applied, with questions of sociodemographic and professional characterization and open questions about the perception of nurses and about the factors that influence family functioning during the COVID-19 Pandemic. We used a “Snowball” sampling process obtaining 51 responses. Content analysis was used as technique for data analysis. Results: participant's perceive families as owning more strengths than weaknesses in their internal environment to cope with changes imposed by the pandemic, and also more opportunities in the external environment, than threats. Conclusion: strengths are opportunities and resources for nurses to empower families skills to overcome weaknesses, supporting an important strategy for provide care centered on the family as a unit.